Comparative Analysis of the Use of Traditional and Digital Media in Introducing Local Cultural Heritage to the Younger Generation - Hasanah, Amalia; Nurha, Nurhayati (Kampret Journal, 2025)
This research examines the comparative effectiveness of traditional and digital media in introducing local cultural heritage to the younger generation. With the rapid digitalization of media consumption, it is crucial to understand how different media forms influence the preservation and promotion of cultural heritage among youth. The study explores the strengths and limitations of traditional media (e.g., TV, radio, print) and digital media (e.g., social media, online platforms, mobile apps) in fostering engagement with cultural heritage. Findings suggest that while traditional media remains an authoritative source for cultural knowledge, it struggles to capture the attention of younger audiences, who prefer the interactive, engaging nature of digital media. On the other hand, digital media offers greater flexibility and reach but faces challenges related to content authenticity and fragmentation. A hybrid approach combining both media forms is recommended to effectively promote local cultural heritage, with a focus on creating engaging, interactive, and educational content that resonates with youth. The research highlights the need for collaboration between cultural institutions, educators, and media producers, as well as the importance of policy actions supporting media literacy, local content creation, and cross-media campaigns. This study contributes to the understanding of how media can be strategically used to preserve and promote cultural heritage in the digital age.